Nationality Thought in Developing Critical Education - A. A. Gde Putera Semadi (Dwijendra University, 2021)
Critical education has a very strategic role in supporting and accelerating the formation of a civilized democratic society. Its existence is able to change the world, create the culture, carve out the history, engineer the world to be more fair and humane, even to change concepts, ideas, systematics, and strength. Implementation of critical education is based on three dimensions: the pedagogic practical, normative, and cultural ideology dimensions. Critical education process is formulated as a process of cultural dimension. The main function and target of critical education is